THE COMPETENCIES AND STRATEGIES ADOPTED BY AIR LINES - Johar; MGM; Yajid, Mohd Shukri Ab; Azam, S.M. Ferdous (International Journal of Psychosocial Rehabilitation, 2020)
The purpose associated this work is to examine the adopted polices and measures by the Airlines in Malaysia. The rebirth of this carrier was in the aftermath of September 11, 2001 tragedy crisis and terrorist attack in New York. Air Asia has succeeded in turning around in the airline industry from a losing airline into a strong growth and profitable airline, especially in having a track record of achieving success during an extraordinary difficult period for the airline industry, that was caused by the adverse effect of terrorist attacks, the wars in Afghanistan and Iraq, the Severe Acute Respiratory Syndrome (SARS), tsunami incidence and rising fuel prices and insurance premiums. The Air Asia group strategically focuses on providing high frequency services on point-to-point short-haul routes within a three-and-half hour flight time from its domestic and international hubs. All these have been made available with the use of technology to meet its commitment for “Easy to Book, Easy to Pay, Easy to Fly” while reducing cost and increasing customers and market share. With that Air Asia cost per ASK1 is reducing every year and its cost per ASK is the lowest globally. Air Asia adopted the models of the very successful Southwest Airlines from the US and Ryan Air and Easy jet from Europe but with added emphasize on technology. Its successful and proven low-cost model in Malaysia was replicated across boarder. In 2004, Air Asia formed two successful joint ventures in Thailand and Indonesia as low fare airline. To date, the Air Asia Group has carried over 11 million passengers and currently operates over 100 domestic and international daily flights from its hubs.